Uji Efektifitas Jamur Beauveria bassiana Bals. terhadap Ulat Grayak (Spodoptera litura F.) pada Tanaman Tembakau - ANANDA RIZKI NURANI; I PUTU SUDIARTA; NI NENGAH DARMIATI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
The Effectiveness Test of Fungus Beauveria bassiana Bals. against Armyworm (Spodoptera litura F.) on Tobacco Crops Tobacco crops is one of the national commodity and plays an important role for Indonesian economy. Various attempts of cultivation technique have been implemented. However, obstruction are found on tobacco cultivation, one of them is armyworm (Spodoptera litura F.) pest. The effort of controlling the pests is still using chemical technique while in fact it leds to negative impact to living beings and environment. Therefore, eco-friendly control using fungus Beauveria bassiana Bals. in the form of formulation are necessary. This study was conducted to determine the quality and effectiveness of B. bassiana formulation obtained from Estate Crops Service of Bali Province against armyworm (S litura). Research method of this study was using a randomized block design with 5 treatments and 5 replicates. This treatment was using concentration of 60 grams, 45 grams, 30 grams, 15 grams formulation dissolved in one liter of water and the control of using water only. The observed variable was the mortality and intensity of armyworm attacks (S. litura). The result of this study showed that the formulation of fungus B. bassiana has characteristics in which the colonies are white, round-shapes spores, grape-shaped structure and the density of a spore is 1 x 107 spores/ml, therefore it considered it has a good quality. B bassiana formulation is able to infect armyworm (S. litura) on the fourth day. Efficacy test in the green house of 60 grams concentration dissolved in one liter of water showed a good result, with the highest mortality and the lowest damage intensity of tobacco crops.